POLA MAKAN DAN EFEKTIFITAS EDUKASI TERHADAP PERUBAHAN PENGETAHUAN REMAJA PUTRI TENTANG ANEMIA DI KOTA KUPANG - Maria Goreti Pantaleon; Asweros Umbu Zogara (CHMK HEALTH JOURNAL, 2023)
Iron Nutritional Anemia is Anemia that arises due to iron deficiency so that the formation of red blood cells and other functions in body disrupted. Nutritional anemia is very common in Indonesia an occur in every age groups. Riskesdas 2018 found that is increase in cases of anemia in young women. In 2013, there is 37,1 percent of young women experienced anemia. The largest proportion of anemia occurs in the age group 15 – 24 years, and those aged 25 to 34 years. The purpose of this study was to describe the diet of young women, and to analyze the effectiveness of nutrition education on increasing the knowledge of young women about nutritional anemia in Kupang City. The sample in this study were 30 young women. The research was conducted in May until October 2022. The result found that there were differences in knowledge before and after being given education with a value of p = 0.000, and the results of the analysis of the effectiveness of educational methods on changes in knowledge showed that there were no significant differences of three methods on changes in knowledge of young women p = 0.532. to describe the dietary pattern of respondents, it is known that the highest energy consumption is in the sufficient category (43.33%), the highest protein consumption in in the sufficient category (33,33%), and the highest iron consumption in in the less category (93,33%). Keywords : Iron Deficiensy, Knowledge, and Diet